Drug eluting stents: an updated meta-analysis of randomised controlled trials. Issue 5 (10th October 2005) - Roiron, C; Sanchez, P; Bouzamondo, A; Lechat, P; Montalescot, G
Abstract : Objective: To confirm the overall benefit of drug eluting stents (DES), to evaluate the effect of different DES, and to assess the global safety of DES compared with bare stents through a meta-analysis of randomised controlled trials. Methods: Randomised controlled trials comparing sirolimus and derivates or paclitaxel and derivates eluting stents versus bare stents. Binary restenosis and major adverse cardiac events (MACE) were chosen as primary end points. Death, Q wave myocardial infarction (MI), and stent thrombosis up to 12 months' follow up were also analysed. Results: MACE overall occurrence was highly reduced with DES from 19.9% to 10.1% (odds ratio (OR) 0.46, 95% confidence interval (CI) 0.41 to 0.52, p < 0.001). A significant heterogeneity (p < 0.001) was found between subgroups according to the drug: MACE OR was 0.28 (95% CI 0.22 to 0.35) in the sirolimus subgroup and 0.62 (95% CI 0.53 to 0.73) in the paclitaxel subgroup. Restenosis was also highly reduced from 31.7% with bare stents to 10.5% with DES (OR 0.25, 95% CI 0.22 to 0.29, p < 0.001) with a similar heterogeneity between subgroups. Mortality, Q wave MI, and stent thrombosis were not significantly different between DES and control group, whereas Q wave MI and stent thrombosis tended to be more frequent with paclitaxel. Conclusion: This meta-analysis confirms the overall benefit of DES on restenosis and MACE with significant heterogeneity between drugs, suggesting higher efficacy of sirolimus eluting stents. Additional data with longer follow up and in high risk populations are needed to clarify issues on stent thrombosis.